2015
DOI: 10.2463/mrms.2014-0104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Regional White Matter Volume Reduction after Diffuse Axonal Injury using Voxel-based Morphometry

Abstract: Purpose: We developed a new and convenient method that employs voxel-based morphometry (VBM) to evaluate regional reduction in the volume of white matter after diffuse axonal injury (DAI).Methods: We studied 29 patients with moderate cognitive disability after DAI. Each subject underwent 3-dimensional volumetric magnetic resonance (MR) imaging. Images were preprocessed automatically using stand-alone software running on a Windows PC for VBM of volumetric MR imaging utilizing a statistical parametric mapping (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recently, advanced neuroimaging techniques have been used in DAI patients; for example, voxel-based morphometry analysis for volumetric MR imaging detected marked volume reduction in several WM areas in a patient with DAI, [ 9 ] and diffusion tensor imaging showed that the abnormal metrics of diffusion tensor imaging may correlate with the timing of head injury, severity biomarkers and long-term prognosis. [ 10 ] A study of executive control tasks using functional MRI confirmed that augmented functional recruitment may be a neural marker of capacity or efficiency limits in chronic-stage, moderate-to-severe DAI patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, advanced neuroimaging techniques have been used in DAI patients; for example, voxel-based morphometry analysis for volumetric MR imaging detected marked volume reduction in several WM areas in a patient with DAI, [ 9 ] and diffusion tensor imaging showed that the abnormal metrics of diffusion tensor imaging may correlate with the timing of head injury, severity biomarkers and long-term prognosis. [ 10 ] A study of executive control tasks using functional MRI confirmed that augmented functional recruitment may be a neural marker of capacity or efficiency limits in chronic-stage, moderate-to-severe DAI patients.…”
Section: Introductionmentioning
confidence: 99%
“…[7] These studies suggested that the subcortical region, the corpus callosum, the brain stem and the cerebellum were common vulnerable areas in patients with DAI, but the condition is not restricted to the white matter (WM) structures. [8] Recently, advanced neuroimaging techniques have been used in DAI patients; for example, voxel-based morphometry analysis for volumetric MR imaging detected marked volume reduction in several WM areas in a patient with DAI, [9] and diffusion tensor imaging showed that the abnormal metrics of diffusion tensor imaging may correlate with the timing of head injury, severity biomarkers and long-term prognosis. [10] A study of executive control tasks using functional MRI confirmed that Editor: Neeraj Lalwani.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, advanced neuroimaging techniques have been used in DAI patients; for example, voxel-based morphometry analysis for volumetric MR imaging detected marked volume reduction in several areas of the white matter in a patient with DAI [5]. Diffusion tensor imaging (DTI) showed abnormal metrics of DTI might correlate with the timing of the head injury, severity biomarkers and long-term prognosis [6].…”
Section: Introductionmentioning
confidence: 99%